Change in blood pressure status defined by 2017 ACC/AHA hypertension guideline and risk of cardiovascular disease: results of over a decade of follow-up of the Iranian population - Kabootari, Maryam; Tamehri Zadeh, Seyed Saeed; Hasheminia, Mitra; Azizi, Fereidoun; Hadaegh, Farzad (Frontiers in Cardiovascular Medicine, 2023)
Background Hypertension (HTN) is known to be the leading cause of cardiovascular disease (CVD) and mortality. We aimed to assess the impact of changes in 3 years in different blood pressure (BP) categories on incident CVD. Methods In this study, 3,685 Tehranians aged ≥30 years (42.2% men) free of prevalent CVD with BP level <140/90 mmHg and not on BP-lowering medications were enrolled. Participants were grouped according to baseline BP category using the 2017 ACC/AHA hypertension guideline definition: normal BP (<120/80 mmHg), elevated BP (120–129/<80), and stage 1 HTN (130–139 and/or 80–89). The hazard ratio of incident CVD by changes in the BP category was estimated after adjustment for traditional risk factors using Cox's proportional hazard model, with stable normotension as a reference. Results During a median follow-up of 11.7 years, 346 CVD events (men = 208) occurred. Compared to the reference group, among participants with normal BP at baseline, only those with BP rising to stage 1 HTN [1.47 (0.99–2.16)], and among those with stage 1 HTN at baseline, regression to elevated BP [1.80 (1.11–2.91)], remaining at stage 1 [1.80 (1.29–2.52)], and progression to stage 2 HTN [1.81 (1.25–2.61)] had a higher risk for CVD; however, regression to normal BP attenuated this risk [1.36 (0.88–2.12)]. Conversion from elevated BP to any other categories had no significant association with CVD risk. Conclusions Generally, prevalent stage 1 HTN (regardless of changing category) and incident stage 1 HTN were significantly associated with a higher risk of CVD; even regression to elevated BP did not attenuate the risk. Accordingly, these populations are potential candidates for antihypertensive management.